2012
DOI: 10.1111/j.1365-2893.2012.01599.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of response to entecavir therapy in patients with HBeAg‐positive chronic hepatitis B based on on‐treatment HBsAg, HBeAg and HBV DNA levels

Abstract: Quantitative hepatitis B surface antigen (HBsAg) and hepatitis B e antigen (HBeAg) assays are emerging as effective tools of on-treatment predictors of response to antiviral agents, in addition to monitoring serum HBV DNA levels. However, the dynamic relationship between quantitative HBsAg, as well as HBeAg and HBV DNA, and the predictability of subsequent clinical outcomes during entecavir (ETV) therapy remain unclear. Eighty-two patients with HBeAg-positive chronic hepatitis B (CHB) received ETV therapy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
5
20
1
Order By: Relevance
“…Our data showed that both HBeAg titer as well as its declined value at 24-wk were independent predictors for 96-wk HBeAg SC, and it strongly predicted HBeAg SC with an AUROC of 0.928 if combining HBeAg titer < -0.5 lg PEIU/mL and declined value > 2.2 lg PEIU/mL at 24-wk. A study from Shin et al[11] revealed that HBeAg titer < 0.62 lg PEIU/mL after 48 wk of ETV therapy was a strongest predictor for HBeAg SC at year 3 with an AUROC of 0.86 ( P < 0.001), which was inferior to the combined prediction validity of HBeAg level and declined value at 24-wk in our study (AUROC = 0.928). Our study presented that 88% (7/8) of patients with HBeAg titer < -0.5 lg PEIU/mL and declined value > 2.2 lg PEIU/mL at 24-wk achieved 96-wk HBeAg SC, whereas only 2% (1/51) of patients without meting above standards obtained HBeAg SC, thus got a NPV of 98%.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Our data showed that both HBeAg titer as well as its declined value at 24-wk were independent predictors for 96-wk HBeAg SC, and it strongly predicted HBeAg SC with an AUROC of 0.928 if combining HBeAg titer < -0.5 lg PEIU/mL and declined value > 2.2 lg PEIU/mL at 24-wk. A study from Shin et al[11] revealed that HBeAg titer < 0.62 lg PEIU/mL after 48 wk of ETV therapy was a strongest predictor for HBeAg SC at year 3 with an AUROC of 0.86 ( P < 0.001), which was inferior to the combined prediction validity of HBeAg level and declined value at 24-wk in our study (AUROC = 0.928). Our study presented that 88% (7/8) of patients with HBeAg titer < -0.5 lg PEIU/mL and declined value > 2.2 lg PEIU/mL at 24-wk achieved 96-wk HBeAg SC, whereas only 2% (1/51) of patients without meting above standards obtained HBeAg SC, thus got a NPV of 98%.…”
Section: Discussioncontrasting
confidence: 90%
“…The average declines in anti-HBc levels were comparable between the two studies, although the baseline anti-HBc level was relatively higher in our study. Concerning the dynamic change of HBeAg, Shin et al[11] reported that HBeAg level reduced from baseline 2.23 lg PEIU/mL to 0.96 lg PEIU/mL after 96-wk ETV therapy and 17.1% (14/82) achieved HBeAg SC. In the present study, HBeAg level decreased from baseline 2.24 lg PEIU/mL to 96-wk 0.20 lg PEIU/mL and 19.7% (15/76) obtained HBeAg SC, which presented comparable HBeAg reduction and HBeAg SC rate as compared to Shin’s study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors in this study that did impact upon HBeAg seroconversion in univariate analysis included age, ALT, degree of fibrosis and baseline levels of HBV DNA and HBsAg. These have been identified before as baseline characteristics favouring HBeAg seroconversion, and likely reflect the presence of active pre‐existing immune responsiveness at the time of treatment initiation …”
Section: Discussionmentioning
confidence: 86%
“…It was reported that during antiviral treatment, regardless of the nucleoside analog or IFN (PEG‐IFN), HBV DNA and/or HBeAg on‐treatment levels could accurately predict HBeAg seroconversion and long‐term treatment responses in HBeAg‐positive patients [Hsu et al, ; Mommeja‐Marin et al, ; van der Eijk et al, ; Yuen et al, ; Fried et al, ; Buster et al, ; Liaw et al, ; Shin et al, ]. However, our understanding of the prediction of spontaneous HBeAg seroconversion is limited.…”
Section: Discussionmentioning
confidence: 99%